PENGARUH PERTUMBUHAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN RISIKO BISNIS SEBAGAI VARIABEL MODERASI - Fiqry Fachrezzy Putra; Jonnardi (Jurnal Kontemporer Akuntansi, 2025)
The purpose of this study was to examine the effect of company growth, leverage, and profitability on firm value moderated by business risk, property and real estate sector companies listed on the Indonesia Stock Exchange in 2019-2022. The research method used is multiple regression analysis using EViews 12. The results showed that only the leverage variable has a significant effect on firm value and the role of business risk in moderating leverage on firm value on the Indonesia Stock Exchange, then for variables that have no significant effect on firm value, namely company growth and profitability and the role of business risk in moderating the relationship between company growth and profitability on firm value.